DEVELOPING FLUID LEVEL SENSOR BASED ON NON-BEND SHAPED POLYMER OPTICAL FIBER (POF) - MULIYANA IIS; Kuswanto Heru (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2016)
This study aims to determine the effect of the height of the fluid sensing length , the effect of coating onthe cladding of the optical power output , and to determine the best sensitivity and linearity in the fluid levelsensor .Optical fiber used was Polymer Optical Fiber ( POF ) Type SH - 4001-1.3 . Polymer Optical Fiber corehas a refractive index of 1.49 and the cladding refractive index of 1,41. Treatment stripping the protectivejacket with a length of 1.5 cm , 3 cm , 4 cm , and coated with aluminum or copper cladding affects the opticalpower output. Optical power output optical power of POF detected using Optical Power Meter ( OPM ) . Thelight source used was helium neon laser with a wavelength of 632.8 nm and output power of 5 mW .The results showed that the long sensing POF affects optical power output when the height of the fluidbe changed even though the changes are very small . Coating cladding using aluminum or copper can causeweakening of POF optical power , but when coated with copper cladding has a lower attenuation thanaluminum. Best sensitivity values contained in the coated copper sensing with sensing width of 1.5 cm . Bestlinearity is sensing sensing coated aluminum with 2 cm length .Keywords : Polymer Optical Fiber ( POF ) , optical fiber sensors , fluid height